Competing Risks Analysis of Cancer-associated Recurrent Thrombosis, Major Bleeds, and Death in a Geriatric Cohort - Joshua D. Brown; Kelley L. Ratermann; Kelley L. Ratermann; Jeffery C. Talbert; Jeffery C. Talbert; Val R. Adams; Val R. Adams (Journal of Health Economics and Outcomes Research)
**Background:** Individuals with cancer are at an increased risk of venous thromboembolism (VTE). There is a continued increased risk of recurrent VTE after the initial event as well as increased bleed risk related to VTE treatment.